Assessment of acoustic-mechanical measurements for texture of French fries: Comparison of deep-fat frying and air frying - Gouyo, Têko; Mestres, Christian; Maraval, Isabelle; Fontez, Bénédicte; Hofleitner, Céline; Bohuon, Philippe (Food research international, 2020)
[Display omitted] •Combination of acoustic and penetration tests are used to evaluate French fries texture.•A high correlation exists between the sensory crispness and the acoustic parameters.•The NSP and the Fmax makes it possible to clearly identify the crispness.•Deep-fat fried products are crispier than the air fried products with the same water loss. The aim of this study was to develop an instrumental method for measuring the texture of French fries and correlated it with sensory measurements. For seven samples of French fries with different crispness levels, a cone penetrometer test was conducted simultaneously with microphone recording of sound emissions. A descriptive sensory analysis was also performed on these samples. The results showed that the number of sound peaks, the linear distance of sound peaks, the area under the sound-displacement curve and the mean sound pressure were strongly positively correlated (r ≥ 0.80; P-value < 0.02) with the crispness of the crust descriptor. The number of force peaks and the linear distance of the force peaks were correlated with all the acoustic parameters. These two mechanical parameters and the maximum force, were not correlated with crispness of the crust (r = 0.50; P-value < 0.05) but strongly correlated with product hardness (r = 0.9; P-value < 0.01). However, the combination of the acoustic and mechanical parameters appeared suitable for measuring the texture of French fries. An analysis of the variable importance by random forest showed that the main parameters for quantifying the texture differences were the number of sound peaks and the maximum force. The use of this instrumental method and sensory analysis showed that the deep-fat fried products were crispier than the air fried products with the same water loss.